Surgical Sepsis of Hepatobiliary Origin: Cоmplications and Prognosis - Polina Marinova (Journal of Biomedical & Clinical Research)
Hepatobiliary sepsis and biliary septic shock are defined as a group of purulent-inflammatory diseases of the biliary tract which, in their progression, lead to sepsis in case of delayed diagnosis and treatment. The study aimed to analyse all the cases of hepatobiliary sepsis treated at the Clinic of Surgery, Dr G. Stranski University Hospital – Pleven, from 2016 to 2020 and create a reliable prognostic score for surveillance for patients with hepatobiliary sepsis. Retrospectively, we analysed the records of 697 patients (81%) with a hepatobiliary tract infection, including 79 (11.3%) diagnosed with hepatobiliary sepsis and six fatal cases (1.3%). We evaluated all statistically significant factors that affected mortality: immune deficiency comorbidity (р